Assessment of Study Skills and Requirements in Learning Medical Curricula among Medical Students in Gadag District, Karnataka - Ananthachari KR; Rekha Sonavane (Medsci Publications, 2017)
Background: Sudden drift from the schooling and college life to medical profession professional environment makes students difficult to cope up with the study concepts. Study skills are those strategies or skills like making notes, using mnemonics, group discussions and various retention and relaxation techniques for effective learning. Methods: Cross sectional study was conducted among all medical students to elicit the information regarding the various study skills and strategies like preferable factors, environmental factors, innovative techniques and requirements for effective learning. Results: Majority of the students think that following time table, breaking study time into bits, finishing the work on the day, reading in morning and library, use of posters, charts and internet for difficult topics will help in better learning. Teacher should be interactive, loud, clear and use innovative techniques while teaching Conclusion: Student's perspective thinking about the factors like following time schedule, use of innovative and relaxation techniques and requirements from teachers are all important factors in better learning of the medical curricula.